Development and validation of a home-based exercise program integrated with patient education based on the health belief model for patients with type 2 diabetes mellitus - Mustapa, Nurul Amirah; Alghwiri, Alia; Manaf, Haidzir (Nova Southeastern University, 2025)
Purpose: The purpose of this study is to develop and validate a comprehensive approach that integrates an exercise routine with patient education based on the health belief model (HBM) approach to promote effective exercise in this population. Method: A 3-phase study was conducted. In Phase I, two comprehensive scoping reviews were performed to develop the program. An initial draft of the program consisted of exercise protocols and HBM-based education. In Phase II, nine experts were chosen to further develop and refine the program’s content by providing feedback and validating it using the content validity index (CVI) and the Patient Education Material and Assessment Tool (PEMAT). In PHASE III, 15 T2DM patients were invited to evaluate the program instruments using the face validity index (FVI). Results: The program demonstrated excellent content and face validity. The proposed program included the safety sheets related to the exercise and participant booklets. It also consisted of four 60-minute education sessions, with a combination of home-based aerobic and resistance exercises over a 12-week duration. Conclusions: The proposed program shows strong validity for patients with T2DM, making it a promising intervention for primary care and community settings. The inclusion of the HBM as a theoretical underpinning contributes to understanding exercise behavior and enhances the feasibility and effectiveness of the intervention.